Prototype Design of Adaptive Composite Springs As An Anti-Seismic Infrastructure System For Multi-Story Buildings - Auni Zahratu Syifa; Naziha Alqiara; Muhammad Fakhri; Muhammad Ghaziyan Faizan; Afryansyah Afryansyah (LKP Unity Academy, 2025)
This study aims to design and formulate earthquake dampers composed of carbon fiber and epoxy resin, employing a specialized configuration to produce anti-seismic devices that are corrosion-resistant, adaptively flexible, and capable of supporting building loads effectively. A quantitative design-based methodology was applied, encompassing prototype design, material selection, and performance testing against vertical loads and seismic vibrations. Evaluation was conducted using a hydraulic press to determine maximum vertical load capacity and a shake table to simulate horizontal and vertical seismic activity according to the Richter scale. The results indicate that the composite dampers can absorb seismic energy bidirectionally, maintain structural integrity without significant material degradation, and require minimal maintenance. These findings demonstrate the potential of carbon fiber and epoxy resin-based dampers as adaptive seismic isolation systems that are robust, durable, and suitable for multi-story buildings, while meeting the demands for economical, efficient, and sustainable infrastructure solutions.